Imidacloprid residue in paddy, unpolished and polished rice, and health risk assessment of rice consumption in Tanjung Karang, Malaysia - Chokeli, Raihanah (2015)
Background: Rice (Oryza sativa L.) by large is staple food consumed and produced by most of the world population including Malaysia. In order to combat from brown planthoppers attack, farmers have used imidacloprid in the paddy fields. However, the used of imidacloprid might give some effect to the population that consume rice. Objective: The objective of this study was to evaluate the non-carcinogenic health risks on Tanjung Karang’s population (n=552) through rice consumption. Methodology: Fifty samples of paddy, unpolished rice and polished rice were collected from paddy fields and milling factory in Tanjung Karang, Selangor and were analysed for imidacloprid residues. The population was divided into 3 age groups which are adult, teenagers and children. Imidacloprid residue analysis in paddy and rice samples was conducted using the simplified and validated QuEChERS (quick, easy, cheap, effective, rugged, and safe) preparation method. Samples were extracted with acetonitrile (ACN) and salts anhydrous magnesium sulphate (MgSO4) and sodium chloride (NaCI) while cleaning was by treating with primary secondary amine (PSA). Imidacloprid residue was quantified with Ultra High Performance Liquid Chromatography (UHPLC) using C18 column and UV detector. The method was validated in term of linearity, range, limit of detection (LOD), limit of quantification (LOQ), precision (repeatability and intermediate precision), and accuracy (recovery). LOD and LOQ and of the method was 0.001 mg/L and 0.003 mg/L, respectively. Result: The validated method provides good analytical results wherein the linearity r2 was 0.9996, recoveries 80−120 % and RSDs <20%. Through of this method, imidacloprid residue was detected in 20%, 14% and 10% of paddy samples, unpolished rice and polished rice, respectively with 4% of the total samples exceeded the MRL. The mean imidacloprid concentration was 0.14 mg/kg in the paddy sample, 0.04 mg/kg in unpolished rice sample and 0.03 mg/kg in polished rice sample. The EDI for adult, adolescent and children were 0.08 mg/kg, 0.03 mg/kg and 0.0002 mg/kg, respectively. HQ value of adult was 1.32 showed that this group was exposed to non-carcinogenic health risk through rice consumption. Conclusion: The result of analysis showed that imidacloprid residues were present in paddy and rice samples originate from Tanjung Karang paddy cultivation area. Imidacloprid was detected in mostly in paddy samples compared to brown rice and white rice, respectively with 4% of the total samples exceeded the Malaysian Residue Level (MRL). This indicates that routine monitoring of this contaminants in food items is required to prevent, control and reduce the contamination and to minimize health risks. This research has provided important information on imidacloprid residues contamination on local paddy and rice for the first time.